Education and Wage Inequality in Germany: A Review of the Empirical Literature - Andrea Maria Weber; Andreas Ammermüller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper reviews the current state of knowledge on the link between education and wage inequality in Germany. The wage inequality is characterized by its stability, although a more detailed analysis reveals structural differences, especially between East and West Germany. Both the between and within educational levels wage inequality changed little over time, while there are some tendencies of a converging distribution of education. A need for further research is identified in the effects of education on wage inequality in separate cohorts as well as the direct links between the two distributions in Germany.
Keywords: 330; Lohnstruktur; Lohndifferenzierung; Bildungsniveau; Familiensoziologie; Bildungschancen; Deutschland; Neue Bundesländer